1997
DOI: 10.2337/diab.46.6.1081
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mutations and a Mutational Hotspot in the M0DY3 Gene

Abstract: Maturity-onset diabetes of the young 3 (MODY3) is a type of NIDDM caused by mutations in the transcription factor hepatocyte nuclear factor-la (HNF-la) located on chromosome 12q. We have identified four novel HNF-la missense mutations in M0DY3 families. In four additional and unrelated families, we observed an identical insertion mutation that had occurred in a polycytidine tract in exon 4. Among those families, one exhibited a de novo mutation at this location. We propose that instability of this sequence rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…For all these patients the mutated gene had not been analyzed previously. Two patients harbored missense mutations in the HNF1A gene that were previously reported in patients with MODY3 [35,36]; the c.586A>G (p.Thr196Ala) identified in a 3 year old male patient with “prediabetes” (Table 2, patient 28) was also found in his 12 year old brother with a similar glucose pattern. Mutations in GCK were identified in 10/44 cases with a MODY phenotype (23%) (Table 2, patients 29–38); 4 of them are novel to this study and predicted to be damaging by in-silico predictions (Supplementary Table 4).…”
Section: Resultsmentioning
confidence: 83%
“…For all these patients the mutated gene had not been analyzed previously. Two patients harbored missense mutations in the HNF1A gene that were previously reported in patients with MODY3 [35,36]; the c.586A>G (p.Thr196Ala) identified in a 3 year old male patient with “prediabetes” (Table 2, patient 28) was also found in his 12 year old brother with a similar glucose pattern. Mutations in GCK were identified in 10/44 cases with a MODY phenotype (23%) (Table 2, patients 29–38); 4 of them are novel to this study and predicted to be damaging by in-silico predictions (Supplementary Table 4).…”
Section: Resultsmentioning
confidence: 83%
“…In this study, we reported a HNF1A-MODY family with a missense mutation in the exon 4 of HNF-1A gene c.779 C>T (p.T260M) which was first reported in 1997 [19], but it was the first time to be detected in Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…В исследовании, прове-денном в двух национальных центрах Словакии и Чехии, при обследовании пробандов без отягощен-ной наследственности выявлено 4 случая мутации de novo и 1 случай бессимптомного носительства му-тации HNF1a. Также ранее были описаны еще два случая мутации de novo -p.P291fs [24,25].…”
Section: Discussionunclassified